PENGARUH SOSIAL MEDIA PEMASARAN TERHADAP PENJUALAN HASIL INDUSTRI KERAJINAN TENUN SONGKET RUMAHAN DI LOMBOK TENGAH - Lale Puspita Kembang; Mahmud; Lalu Delsi Samsumar (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
Central Lombok is known as a center for songket woven fabric craftsmen, and has experienced ups and downs in terms of sales. Many factors cause the problem to occur, including the location of craftsmen and potential buyers relatively far from major roads, minimal promotions, high fees for guides and partners, inappropriate prices for goods, and so on. The purpose of this study was to determine the effect of social media marketing on the increase in sales volume of the home-made songket woven fabric industry in Central Lombok. This type of research is survey research, carried out using a questionnaire with a Likert scale. The sampling technique used was purposive sampling. The results showed that the independent variable Facebook has a positive effect on sales. WhatsApp has a positive effect on sales volume. Twitter has a positive effect on sales. Instagram has a negative effect on sales.